Isolate - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Grand illusion, 2022)
"Industrialization. Social unrest. Underground movements. Government corruption and surveillance. Something is about to give. Steffan Dekkard is an isolate, one of the small percentage of people who are immune to the projections of empaths. As an isolate, he has been trained as a security specialist and he and his security partner Avraal Ysella, a highly trained empath are employed by Axel Obreduur, a senior Craft Minister and the de facto political strategist of his party. When a respected Landor Councilor dies of "heart failure" at a social event, because of his political friendship with Obreduur, Dekkard and Ysella find that not only is their employer a target, but so are they, in a covert and deadly struggle for control of the government and economy. Steffan is about to understand that everything he believed is an illusion."--